1982
DOI: 10.4141/cjps82-058
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Leaf Frost Resistance to the Winter Survival of Seedling Stands of Alfalfa

Abstract: Plants propagated from single plant selections of the alfalfa cultivars Saranac and Luna (Medicago sativa L.), Beaver (M. media Pers.) and Anik (M. falcata L.) were transplanted into the field in May and subjected to a range of freezing temperatures at 3-wk intervals during August and September. A portable field freezing chamber was used to study the influence of frost on leaf injury in the fall and winterkill following the severe 1977–1978 winter. Leaves of all plants had the capacity to harden during the fal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…definition in their alfalfa studies, although in another study they found that leaves of alfalfa seedlings cold acclimate during the fall and survive to about -l0"C (McKenzie and Mclean 1982).…”
mentioning
confidence: 99%
“…definition in their alfalfa studies, although in another study they found that leaves of alfalfa seedlings cold acclimate during the fall and survive to about -l0"C (McKenzie and Mclean 1982).…”
mentioning
confidence: 99%
“…The single warm day in 1997, immediately after seeding, and the week of borderline conditions in 1998 may have allowed some germination to occur. Any seedlings that germinated in the fall would be expected to die when soil temperatures dropped below -2.2°C (McKenzie and McLean 1982). The risk of untimely germination can be somewhat offset with seed treatments to inhibit seed germination in the fall.…”
Section: Discussionmentioning
confidence: 99%
“…Alfalfa plants possessing high levels of freezing resistance continue to accumulate and store cryoprotective substances at low temperatures, which contribute to the winter survival, thereby lowering the temperature required to kill the plant (McKenzie and McLean 1982). Alfalfa in the western Canadian prairies often continues to harden into December or January under snow.…”
Section: Discussionmentioning
confidence: 99%